(untitled) (Journal of actual problems of jurisprudence, 2021)
The article discusses the actual issues of legal provision of sanitary and epidemiological safety in the Republic of Kazakhstan. It is also very important that in modern conditions, the health of society is largely determined by sanitary and epidemiological well-being, the real provision of human rights, society and the state to a safe environment and disease prevention, and the quality of consumer services. Unfortunately, both the executive branch nor legal science paid sufficient attention to these issues, and there are almost no scientific publications on this issue. The conducted research is fragmentary, and the time is quite outdated. For example, the sanitary legislation itself was comprehensively studied only from the point of view of the organization of health and social hygiene. These issues have not been subjected to a comprehensive and comprehensive analysis in the legal literature, within the framework of special scientific legal studies. In these conditions, it is important and necessary to analyze the current sanitary legislation in Kazakhstan and develop proposals for its improvement. Key words: legal support, environmental support, sanitary and epidemiological safety, sanitary and epidemiological welfare of the population, sanitary and epidemiological rules and regulations.